A high-heat-stable transparent copolyester modified with a blocked aliphatic isocyanate and a method for preparing the same
Patent Information
- Application Number
- CN202611462009.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0014]鉴于上述和/或现有商用PETG、PCTG透明共聚聚酯存在高温下热稳定性较差、湿热易水解断链、溶剂介质下抗环境应力开裂性能较差、易老化开裂的问题,解决传统直接利用异氰酸酯改性易发生预反应形成凝胶,且发黄、长效耐久度不足等技术瓶颈,针对现有工业化注塑量产工况,提出了本发明
[0030](1)本发明改善了传统单一助剂改性、常规酚类封闭的工艺,依托大位阻耐耐高温脂环叔醇,对异氰酸酯单体钝化封端,协同碳化二亚胺构建防护体系,在保留共聚聚酯高透光、低雾度的基础上,强化聚酯熔体高温流动稳定性、抗溶剂化学应力开裂,兼顾常温长效储存稳定性、工业化无需改线,易进行规模产业化落地。
Smart Images

Figure CN122958689A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a highly thermally stable transparent copolyester modified with end-capped aliphatic isocyanate and its preparation method. Background Technology
[0002] Copolyesters PETG and PCTG are novel transparent polyester materials that have been successfully industrialized in recent years. They are prepared by copolymerizing and block-modifying polyesters with diol monomers such as neopentyl glycol (NPG), 1,4-cyclohexanediethanol (CHDM), bio-based isosorbide ISB, and 2,2,4,4-tetramethylcyclobutanediethanol (CBDO). These copolyesters exhibit excellent visible light transmittance and extremely low haze; good impact toughness; a relatively wide melt processing range, suitable for high and low speed injection molding, extrusion, and thermoforming processes; and are free of plasticizers, non-toxic, sterile, resistant to food oil and grease corrosion, resistant to weak acids and alkalis in daily chemical products, and environmentally compliant. These transparent copolyesters have been widely used in applications such as aseptic food packaging, high-end cosmetic containers, outdoor weather-resistant optical transparent sheets, sterile medical transparent instrument parts, and high-precision injection-molded transparent structural components.
[0003] However, existing commercial-grade PETG and PCTG transparent copolyester materials contain highly reactive and easily broken ester bonds in their main chains, leading to the following problems:
[0004] 1) Poor stability during high-temperature melt processing. At high temperatures or during secondary processing, the viscosity of polyester melt fluctuates greatly and the melt flow drifts over a wide range, resulting in uneven melt flow rate inside the injection mold cavity. This leads to uneven internal stress in the final product, which can easily induce cracking and result in high rework costs during mass production.
[0005] 2) Performance is prone to rapid deterioration in humid or hot or chemical solvent environments: In complex scenarios such as outdoor high humidity rain, underground closed high water vapor storage, daily contact with acid and alkali media, and high and low temperature alternating humid heat cycle, the ester bonds in polyester are prone to hydrolysis and chain breakage, leading to degradation of long chain molecules, reducing the effective winding of chain segments, and the mechanical properties of the product rapidly decline. After long-term use, the product surface turns white and foggy, internal microcracks spread, and edge stress brittle failure occurs, significantly shortening the performance of high-end transparent products.
[0006] Currently, commonly used PET chain extenders mainly include epoxy compounds, acid anhydride compounds, and isocyanate compounds. Their active groups can react with the carboxyl or hydroxyl groups at the ends of PETG, achieving chain extension and effective increase in molecular weight.
[0007] Epoxy compounds, due to their high reactivity, can react efficiently with the carboxyl groups at the ends of polyesters. They also offer advantages such as low cost and no irritating odor, making them a common and highly effective class of plastic modifiers. However, in polyester chain extension modification, they suffer from defects such as difficulty in uniform dispersion, leading to gel formation within transparent ester bonds.
[0008] Among anhydride chain extenders, pyromellitic dianhydride (PMDA) is the most representative. The anhydride functional groups in its molecular structure can react with the hydroxyl groups at the ends of the polyester, thereby achieving chain extension. However, PET modified using this method often suffers from a wide molecular weight distribution and is accompanied by the formation of branched molecular chains.
[0009] Among oxazoline polymers, 1,3-benzene-bisoxazoline and 2,2'-bis(2-oxazoline) are two representative chain extenders. The oxazoline ring in their molecular chain can react efficiently with the terminal carboxyl group of PET through ring-opening addition reactions, thereby achieving effective chain extension and thickening modification, but this is limited by factors such as high cost.
[0010] Carbodiimide-based anti-hydrolysis auxiliaries can also be applied to polyester systems. CN108753146B describes the preparation of an industrial-scale alicyclic polycarbodiimide anti-hydrolysis agent and its application in PET, PBT, and polyester polyol anti-hydrolysis. This agent exhibits low volatility, high temperature resistance, and does not affect transparency, making it suitable for transparent copolyester systems. CN103556291B describes the addition of carbodiimide-based anti-hydrolysis agents to polyester fibers to inhibit ester bond hydrolysis and maintain strength. While carbodiimides capture trace amounts of free carboxyl groups generated during polyester hydrolysis, providing surface passivation protection, they struggle to penetrate deep into the polyester molecular chain to build a cross-linked protective network and strengthen the polyester's main structural framework. This results in short-term protective effects and insufficient long-term durability, leading to rapid failure of protective efficacy after short-term service, making them unsuitable for demanding outdoor applications requiring long-term use.
[0011] Isocyanate groups react efficiently with the hydroxyl and carboxyl groups at the ends of PETG, exhibiting excellent reactivity. Therefore, they are often used as important reactive additives in the field of plastic modification. However, these compounds also have obvious limitations in practical applications, such as a strong odor, poor thermal stability, and easy degradation during high-temperature processing, which to some extent limits their widespread application under high-temperature processing conditions. Traditional isocyanate blocking and passivation systems, such as phenolic isocyanates, can improve the application limitations of isocyanate systems in polyesters, but they still have fatal compatibility defects. Mainstream blocking agents in the industry, such as phenol, nitrophenol, and halogenated phenols, generally have low low-temperature unblocking thresholds, usually below 160°C. They are prone to oxidative cracking during high-temperature processing and are easily oxidized under high-temperature melting conditions to generate conjugated quinone-type strong chromogenic polar groups, directly causing severe yellowing of transparent polyester products and destroying their transparency properties. Therefore, they are not suitable for high-transmittance, low-haze, and low-yellowing high-end transparent copolyester systems. CN110804146A describes the preparation of a storage-stable, low-yellowing blocked isocyanate composition. Commercially available polyisocyanates are first treated with an alkylating agent, and then reacted with an oxime blocking agent. The resulting blocked isocyanate composition exhibits significantly improved color storage stability. After heating with the alkylating agent, the phenolic hydroxyl groups of hindered phenolic substances in the polyisocyanate are alkylated, thereby blocking the formation of highly conjugated structures and chromogenic groups such as nitroso groups. CN102924676A addresses the yellowing and brittleness of polylactic acid by copolymerizing a transparent copolyester, adding 2,4-phenyl diisocyanate during the copolymerization stage for in-situ chain extension. This technology yields a modified copolyester material with a maximum transmittance of 84%, but it is not possible to obtain an optical-grade resin with a transmittance exceeding 88% suitable for transparent parts.
[0012] In summary, existing conventional modification technologies, single chain extender or hydrolysis-resistant additive systems, and traditional closed-passivation systems cannot simultaneously achieve multiple core performance standards, including long-lasting isocyanate-activated end-capping passivation, stable material properties during processing and molding, high substrate transparency, low yellowing, controllable melt flow fluctuations, and good resistance to stress chemical cracking. These limitations hinder the high-quality upgrade of high-end transparent copolyesters. This invention targets commercially available transparent copolyester materials, efficiently improving the high-temperature thermal stability of polyester melts, enhancing the material's comprehensive mechanical properties, and improving its resistance to stress chemical cracking in acid, alkali, and alcohol solvent environments. Furthermore, the material maintains excellent transparency, produces no color-developing byproducts, and retains the substrate's high light transmittance and low haze optical properties. It is compatible with existing mass production equipment and processing techniques for transparent polyester products. Summary of the Invention
[0013] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0014] In view of the above and / or existing problems of poor thermal stability of commercial PETG and PCTG transparent copolyesters at high temperatures, easy hydrolysis and chain scission under humid heat, poor resistance to environmental stress cracking under solvent media, and easy aging and cracking, this invention is proposed to solve the technical bottlenecks of traditional direct modification with isocyanate, such as easy pre-reaction to form gel, yellowing, and insufficient long-term durability.
[0015] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a highly thermally stable transparent copolyester modified with capped aliphatic isocyanate.
[0016] To solve the above-mentioned technical problems, the present invention provides the following technical solutions, including: Aliphatic isocyanates and alicyclic tertiary alcohols react in the presence of an organotin catalyst to obtain a capped isocyanate intermediate; the alicyclic tertiary alcohol capped intermediate is decapped at 210°C or above.
[0017] A modified copolyester is obtained by melt extrusion of a copolyester base material, a capped isocyanate intermediate, an aliphatic carbodiimide anti-hydrolysis agent, and a phosphite antioxidant in a mass ratio of 100:0.3-1.2:0.1-1.0:0.1-0.35; wherein the molar ratio of the effective -NCO functional groups of the alicyclic tertiary alcohol to the isocyanate is 2.03-2.05:1.
[0018] The copolyester base material, the capped isocyanate intermediate, the aliphatic carbodiimide anti-hydrolysis agent, and the phosphite antioxidant work synergistically to significantly improve the stability of the polyester system under high-temperature processing and long-term thermo-oxidative environments, effectively inhibiting yellowing and molecular chain degradation. Among them, the alicyclic tertiary alcohol caps and stabilizes the isocyanate. After high-temperature decapping, the isocyanate reduces catalytic degradation through the residual carboxyl groups at the capping. The high molecular weight carbodiimide continuously neutralizes the generated acidic substances, while the phosphite decomposes hydrogen peroxide and chelates metal ions, forming a multi-level protection mechanism.
[0019] In a preferred embodiment of the method for preparing the end-capped aliphatic isocyanate-modified high-thermal-stable transparent copolyester of the present invention, the aliphatic isocyanate includes one or more of HMDI or IPDI. The aliphatic isocyanates are 1,6-hexamethylene diisocyanate (HMDI), CAS: 822-06-0, structural formula: OCN-(CH2)6-NCO; and isophorone diisocyanate (IPDI), CAS: 4098-71-9, alicyclic structure.
[0020] In a preferred embodiment of the method for preparing the end-capped aliphatic isocyanate-modified high-thermal-stable transparent copolyester of the present invention, the alicyclic tertiary alcohol serves as a blocking agent, containing only a single tertiary hydroxyl group and lacking primary hydroxyl groups, secondary hydroxyl groups, acidic functional groups, and aromatic conjugated structures. It includes one or more of saturated bicyclic alicyclic tertiary alcohols, saturated polymethyl-substituted monocyclic alicyclic tertiary alcohols, and adamantyl alkyl tertiary alcohols. Alicyclic tertiary alcohols possess high steric hindrance, high-temperature resistance, no color development, and excellent compatibility with polyesters.
[0021] The alicyclic tertiary alcohols include borneol (abbreviated as 1SEB, borneol, C) 10 H 18 O, melting point: 204~208℃, boiling point: ~280℃), methyl isobornol (C 11 H 20 O, melting point: 210~213℃, boiling point: ~297℃), camphenic tertiary alcohol (C 10 H 18 O, melting point: 202~206℃, boiling point: ~277℃), 1-adamantanol (molecular formula: C 10 H 16 O, melting point: 208~215℃, boiling point: ~295℃).
[0022] In a preferred embodiment of the method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester of the present invention, the organotin catalyst comprises dibutyltin dilaurate (DBTDL), and the amount added is 0.15 wt% of the alicyclic tertiary alcohol; the phosphite antioxidant comprises tris(2,4-di-tert-butylphenyl) phosphite, CAS: 31570-04-4, as an auxiliary heat-resistant oxygen yellowing agent.
[0023] In a preferred embodiment of the method for preparing the end-capped aliphatic isocyanate-modified high-thermal-stable transparent copolyester of the present invention, the reaction is carried out at a rotation speed of 300–500 r / min, a reaction time of 3.0–3.5 h, a temperature of 75–80 °C, and under inert gas protection, the water content of the reaction system is ≤0.05%. Nitrogen is preferably the inert gas.
[0024] As a preferred embodiment of the preparation method of the end-capped aliphatic isocyanate modified high heat-stable transparent copolyester of the present invention, wherein: the copolyester substrate is PETG or PCTG modified with a third monomer, wherein the third monomer includes one or more of NPG, CHDM, and ISB.
[0025] In a preferred embodiment of the preparation method of the end-capped aliphatic isocyanate-modified high-thermal-stable transparent copolyester of the present invention, the aliphatic carbodiimide anti-hydrolysis agent has a number-average molecular weight ≥ 5000. Its structural formula is ~RN=C=NR~, exhibiting characteristics such as low volatility, non-precipitation, long-term carboxyl group capture, and no impact on transparency. The carbodiimide, in the molten state, reacts with the uncapped -NCO in situ to form a urea-ketimide heterocyclic structure.
[0026] As a preferred embodiment of the preparation method of the end-capped aliphatic isocyanate modified high heat-stable transparent copolyester of the present invention, wherein: the closed mixing is carried out at a speed of 1000-1500 r / min for a time of 6-12 min.
[0027] As a preferred embodiment of the preparation method of the end-capped aliphatic isocyanate modified high heat-stable transparent copolyester of the present invention, wherein: the melt extrusion is carried out using a co-rotating parallel twin-screw extruder, and the temperatures of each zone are: zone 1 preheating section 150-180℃, zone 2 melting section 180-200℃, zones 3-5 200-210℃, and die head discharge constant temperature zone 200-210℃; the entire process is carried out under vacuum degassing and impurity removal, and cooling water is used for uniformly drawn strands to prepare modified copolyester particles.
[0028] Another objective of this invention is to overcome the shortcomings of the prior art and provide a highly heat-stable transparent copolyester modified with end-capped aliphatic isocyanate. This copolyester has the following characteristics: an MFR change rate ≤20% after being kept at 230°C for 10 minutes, light transmittance ≥88%, haze ≤2.5%, and no obvious whitening or microcracks after immersion in a 50% ethanol solution for 60 hours or more.
[0029] Beneficial effects of this invention:
[0030] (1) This invention improves the traditional process of single-agent modification and conventional phenol blocking. It relies on the high steric hindrance and high temperature resistance of alicyclic tertiary alcohols to passivate and end-cap isocyanate monomers and construct a protective system in conjunction with carbodiimide. While retaining the high light transmittance and low haze of copolyester, it enhances the high temperature flow stability of polyester melt and resists solvent chemical stress cracking. It also takes into account the long-term storage stability at room temperature and does not require line modification for industrialization, making it easy to carry out large-scale industrialization.
[0031] (2) The present invention uses alicyclic tertiary alcohol to block highly active -NCO functional groups: using the intermediate product - rigid alicyclic - carbamate, under the low temperature premixing extrusion process at 200℃ or below, and with small side reactions throughout the entire process of room temperature storage, batching, and mixing, the prepared isocyanate modified transparent copolyester functional masterbatch can be directly melt-blended to achieve that the modified copolyester material does not gel, clump, become cloudy, or change color when stored at room temperature for a long time, thus solving the industry pain points of short storage and transportation cycle and large batch fluctuation of isocyanate modified materials.
[0032] (3) The present invention prepares functional masterbatch containing capped isocyanate functional groups or uses it to modify transparent copolyester materials: the functional masterbatch is used to dilute the premixed transparent copolyester or the transparent copolyester modified by it is used directly, and the active isocyanate functional groups are decapsulated at the copolyester processing temperature of 210-250℃; it matches the existing PETG / PCTG melt injection molding processing temperature, and free active -NCO groups can be released during the melt plasticizing stage, minimizing the premature loss of active isocyanate functional groups; the overall modification process is simple, no need to modify the existing extrusion and injection molding production lines, and the overall cost is controllable.
[0033] (4) High-temperature in-situ desealing and release of active isocyanate: The desealed and released active isocyanate will undergo a covalent end-capping / chain extension reaction with the terminal hydroxyl and carboxyl groups of the copolyester molecular chain, terminating the terminal carboxyl or hydroxyl groups generated during the high-temperature processing due to ester bond scission, leading to the autocatalytic chain scission of the long molecular chain. This inhibits the uncontrolled thermal degradation of ester bonds at high temperatures, stabilizes the fluctuation range of melt flow rate, and improves the controllability of injection molded product quality.
[0034] (5) The unsealed active-NCO group reacts mildly and synergistically with the carbodiimide additive: a highly heat-resistant and stable urea-ketone imine heterocyclic protective structure is generated in situ, and the dual function of carbodiimide in real time capturing hydrolyzed carboxyl groups and adsorbing trace amounts of water vapor is superimposed to construct a dual anti-hydrolysis protective barrier of physical cross-linking reinforcement and chemical functional group passivation, which significantly improves the chemical stress aging resistance of the product. Attached Figure Description
[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0036] Figure 1 Infrared spectra of isoborneol (1SEB)-terminated isocyanate intermediate before and after unsealing.
[0037] Figure 2Thermogravimetric curves of pure PETG and PETG co-modified with end-capped isocyanate are shown.
[0038] Figure 3 Typical specimen appearances for pure PETG, modified PETG examples, and comparative examples. Detailed Implementation
[0039] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0040] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0042] Unless otherwise specified, all raw materials used in this invention are commercially available industrial-grade raw materials. These include NPG-modified PETG (Dawn Polymer HF300N), CHDM-modified PETG (Dawn Polymer HF200), CHDM-modified PCTG (Dawn Polymer HF500), and ISB-CHDM composite-modified PCTG (Dawn Polymer HF503).
[0043] Performance testing adopts current national standards, and the testing environment is: constant temperature 23℃, constant humidity 50%RH. Melt flow rate (MFR) follows GB / T3682 standard, tensile / bending and impact mechanical properties follow GB / T1040 and GB / T9341 standards, and light transmittance and haze optical indicators follow GB / T2410 standard.
[0044] High-temperature flow thermal stability test of materials: The melt index was tested and evaluated after being kept at a constant temperature of 230℃ for 10 minutes. The melt index change rate was: (normal melt index - delayed melt index) ÷ delayed melt index × 100%.
[0045] The thermal stability of the material was also evaluated by TGA differential thermogravimetric analysis using a TGA DSC 1STARe system from Mettler-Toledo, Switzerland.
[0046] Chemical stress cracking resistance of materials: The sample was immersed in 50% ethanol solution at room temperature for 10 hours, 24 hours, 36 hours, 48 hours and 60 hours, and the surface of the sample was observed to see if cracking or whitening occurred.
[0047] Example 1
[0048] This embodiment provides a method for preparing a transparent copolyester, specifically as follows:
[0049] Aliphatic isocyanates and alicyclic tertiary alcohols react in the presence of an organotin catalyst to yield a capped isocyanate intermediate, with the molar ratio of effective -NCO functional groups of the alicyclic tertiary alcohol to the isocyanate being 2.03–2.05:1.
[0050] A modified copolyester is obtained by melt extrusion of a copolyester base material, a capped isocyanate intermediate, a high molecular weight aliphatic carbodiimide anti-hydrolysis agent, and a phosphite antioxidant in a mass ratio of 100:0.3~1.2:0.1~1.0:0.1~0.35.
[0051] The modified copolyester particles are transferred to a dedicated injection molding machine. The injection segment temperature is preset to 220-255℃, the mold constant temperature is 40-60℃, and the machine is kept under constant temperature and pressure and cooled at a uniform speed to prepare national standard mechanical property test samples and optical property test plates.
[0052] The modified transparent copolyester material obtained in this embodiment has a melt flow rate (MFR) fluctuation of ≤20%, significantly improving its resistance to chemical aging, light transmittance ≥88%, and haze ≤2.5%. Compared with patent CN102924676A, this invention does not belong to polyester polymerization chain extension, but to non-synthetic stage chain extension, and belongs to modification after melt blending. This invention is a modification of finished particles and does not participate in the esterification / polymerization process. The melt blending modification process significantly reduces the technical threshold and equipment investment. Compared with CN110804146A, this invention uses alicyclic tertiary alcohols to block the isocyanate functional groups, instead of easily yellowing phenols, oximes / pyrazoles. The unblocking intermediate of this invention has a higher unblocking temperature, reaching 200℃, and does not develop color. At the same time, a two-component synergistic effect is formed during processing and molding, and the unblocked NCO and carbodiimide synergistically act to produce urea-ketimine, which is a new synergistic mechanism.
[0053] Example 2
[0054] Based on Example 1, this embodiment optimizes the mass ratio of the copolyester substrate, the capped isocyanate intermediate, the high molecular weight aliphatic carbodiimide anti-hydrolysis agent, and the phosphite antioxidant, setting them to 100∶0.6∶0.3∶0.2, 100∶1∶0.5∶0.2, and 100∶0.6∶0.6∶0.3 respectively.
[0055] The modified transparent copolyester material obtained in this embodiment has an MFR change rate of 15.1~22.7%, a light transmittance of 88.8~89.2%, and a haze of 0.9~1.2%.
[0056] Example 3
[0057] Based on Example 1, this embodiment optimizes the types of aliphatic isocyanates. Specifically, HMDI, IPDI, and HMDI and IPDI compounded in a 1:1 mass ratio are selected to prepare copolyester materials.
[0058] The modified transparent copolyester material obtained in this embodiment has an MFR change rate of 17.4~22.7%, a light transmittance of 88.6~89.2%, and a haze of 0.9~1.1%.
[0059] Example 4
[0060] Based on Example 1, this embodiment optimizes the selection of the copolyester substrate, and prepares a copolyester material by setting an NPG-PETG matrix, CHDM-modified PETG special transparent particles, bio-based ISB-modified PCTG copolyester, and ISB-CHDM bicomponent composite modified PCTG.
[0061] The modified transparent copolyester material obtained in this embodiment has an MFR change rate of 17.4~22.7%, a light transmittance of 88.6~89.2%, and a haze of 0.9~1.1%.
[0062] Example 5
[0063] This embodiment provides a transparent copolyester, specifically: The high-purity alicyclic tertiary alcohol used was isobornol / 2-camphenol (1SEB, CAS No.: 507-70-0, purity: 99%, Jiangxi Xinsen Natural Plant Oil Co., Ltd.) blocked HMDI isocyanate (produced by Covestro); the transparent copolyester matrix used was commercially available conventional NPG modified PETG particles (produced by Dawn Polymer, HF300N); the high molecular weight aliphatic carbodiimide anti-hydrolysis agent (produced by Shanghai Langyi), the phosphite-assisted antioxidant (BASF Irgafos 168); the catalyst was dibutyltin dilaurate (DBTDL, Hanshengshi Fine Chemical Co., Ltd.). The preparation process was carried out according to the following procedure to obtain the modified transparent copolyester product sample.
[0064] 1) Preparation of 1SEB-terminated aliphatic isocyanate intermediate: Under high-purity nitrogen protection, HMDI isocyanate was added to a closed constant-temperature reactor and heated to 80-85℃ at a uniform rate. The mixture was stirred at low speed until the raw material was a homogeneous melt. According to the molar ratio of 1SEB to the effective -NCO functional group of isocyanate of 2.03-2.05:1, high-purity 1SEB raw material premixed with 0.15wt% DBTDL was added in batches and stirred at medium speed of 300-500 r / min for 3.0-3.5 h. The mixture was then allowed to cool naturally to below 60℃, and stored in a container protected from light at room temperature under nitrogen protection to prepare the obtained end-terminated isocyanate intermediate.
[0065] Figure 1 The infrared spectra of isoborneol (1SEB)-terminated isocyanate intermediate before and after unpacking show that IPDI and HMDI are at 2270 cm⁻¹. -1 The characteristic absorption peak of the NCO group is present at this location. After blocking with 1SEB, the corresponding absorption peak of the blocked isocyanate completely disappears at this location, indicating that the NCO groups of the isocyanate are basically completely blocked by HBT. The encapsulated IPDI and HMDI show an absorption peak at 3360 cm⁻¹. -1 The absorption peaks in the vicinity are caused by the stretching vibrations of the NH associated and free states in the urethane bonds formed by the reaction of 1SEB and NCO groups.
[0066] 2) Thorough drying of transparent copolyester: Select transparent copolyester granules as substrate NPG modified PETG; dry continuously for 4-6 hours in a vacuum drying silo at a constant temperature of 70-90℃ and a high vacuum negative pressure environment. After drying, sample and test the moisture content of the substrate. The moisture content is controlled at ≤0.02% to prevent residual moisture from inducing side reactions.
[0067] 3) Multi-component functional additives room temperature high speed premixing: Take thoroughly dried transparent copolyester, self-developed 1SEB end-capped aliphatic composite isocyanate, carbodiimide anti-hydrolysis additive with a number average molecular weight ≥5000, and phosphite auxiliary antioxidant in a mass ratio of 100:0.6:0.3:0.2; put the raw materials into a closed high speed mixer, mix in a closed system at room temperature and pressure, and keep the mixing speed constant at 1000-1500 r / min. Continuously homogenize and mix at high speed for 6-12 minutes. After discharge, the material is uniform in color and free of agglomeration and lumps, and is ready for extrusion.
[0068] 4) Twin-screw melt extrusion granulation: A co-rotating parallel twin-screw extruder is selected, with the following temperatures for each zone: Zone 1 preheating section 150-180℃, Zone 2 melting section 180-200℃, Zones 3-5 200-210℃, and discharge constant temperature section 200-210℃; the entire process is vacuum degassing and impurity removal, and cooling water is used for uniformly drawn strands to prepare modified copolyester granules.
[0069] 5) Injection molding sample preparation: The modified copolyester particles are transferred to a special injection molding machine, the injection segment temperature is preset to 220-255℃, the mold constant temperature is 40-60℃, constant temperature pressure is maintained and uniform cooling is performed to prepare national standard mechanical property test samples and special test plates for optical properties.
[0070] Example 6
[0071] The difference between this embodiment and Example 5 is that the mass ratio of the copolyester matrix, 1SEB-terminated HMDI additive, carbodiimide additive, and phosphite antioxidant is adjusted to 100:1:0.5:0.2. The rest of the preparation process is the same as in Example 5. The modified copolyester is obtained and injection molded to obtain the test sheet.
[0072] Example 7
[0073] The difference between this embodiment and Example 5 is that the type of aliphatic isocyanate is changed to IPDI to prepare high-purity 1SEB blocked IPDI aliphatic isocyanate. The rest of the preparation process is the same as in Example 5 to obtain modified copolyester, and injection molded to obtain test plates.
[0074] Example 8
[0075] The difference between this embodiment and Example 5 is that the modified copolyester formulation was adjusted to 100 parts PETG matrix, 1.0 part 1SEB-terminated IPDI additive, 0.5 parts carbodiimide additive, and 0.3 parts phosphite antioxidant. The remaining preparation process was the same as in Example 5. The modified copolyester was then obtained and injection molded into test sheets. The thermogravimetric curves of pure PETG and the PETG synergistically modified with isocyanate prepared in Examples 5-8 are shown below. Figure 2 As shown.
[0076] Example 9
[0077] The difference between this embodiment and embodiment 5 is that the transparent copolyester matrix is replaced with CHDM modified PETG special transparent particles. The rest of the preparation process is the same as that in embodiment 5. The modified copolyester is obtained and injection molded to obtain the test sheet.
[0078] Example 10
[0079] The difference between this embodiment and embodiment 5 is that the matrix is upgraded to use bio-based ISB modified PCTG copolyester, while the rest of the preparation process is the same as in embodiment 5. The modified copolyester is then injection molded to obtain the test sheet.
[0080] Example 11
[0081] The difference between this embodiment and embodiment 5 is that the special end-capping intermediate is made by compounding HMDI and IPDI in equal mass ratios at a 1:1 ratio, and then by end-capping and composite modification with 1SEB. The rest of the preparation process is the same as that in embodiment 5, and the modified copolyester is obtained by injection molding to obtain the test sheet.
[0082] Example 12
[0083] The difference between this embodiment and Example 5 is that the matrix used is ISB-CHDM two-component composite modified high-end PCTGHF503 transparent copolyester, with 1SEB end-capping IPDI additive; the average temperature in the sample preparation conditions is increased by 10°C compared to Example 5 to ensure the stability of the sample performance. All other preparation processes are the same as in Example 5, resulting in the modified copolyester, which is then injection molded into the test sheet.
[0084] Example 13
[0085] The difference between this embodiment and Example 5 is that the amount of NPG-PETG matrix (100 parts), 1SEB-terminated HMDI additive (0.6 parts), carbodiimide additive (0.6 parts), and phosphite antioxidant (0.3 parts) is increased. The remaining preparation process is the same as in Example 5, resulting in a modified copolyester, which is then injection molded into test sheets. This embodiment increases the amount of composite modifying additives, thus enhancing the protective performance.
[0086] Example 14
[0087] The difference between this embodiment and Example 5 is that 100 parts of NPG-PETG matrix, 0.3 parts of 1SEB-terminated IPDI additive, 0.6 parts of carbodiimide additive, and 0.3 parts of phosphite antioxidant are used. The remaining preparation process is the same as in Example 5, resulting in a modified copolyester, which is then injection molded into test sheets. This embodiment is suitable for high-dosage additive formulations.
[0088] Example 15
[0089] The difference between this embodiment and Example 5 is that 100 parts of NPG-PETG matrix, 0.6 parts of 1SEB-terminated IPDI additive, 0.1 parts of carbodiimide additive, and 0.2 parts of phosphite antioxidant are used. The remaining preparation process is the same as in Example 5, resulting in a modified copolyester, which is then injection molded into test sheets. This embodiment reduces the proportion of additives.
[0090] Example 16
[0091] Copolyester modified masterbatch process: The matrix uses industrially common NPG-PETG granules, which are further ground and thoroughly dried according to the drying process in Example 5. The powder size is controlled at approximately 10-60 mesh, and then vacuum-packed for later use. The preparation of 1SEB-terminated aliphatic isocyanate intermediate and the room-temperature high-speed premixing of multi-component functional additives are consistent with Example 5. The ratio of NPG-PETG matrix, 1SEB-terminated IPDI additive, carbodiimide additive, and phosphite antioxidant is 100:6:3:0.3.
[0092] For twin-screw melt extrusion granulation of masterbatch: For thoroughly dried transparent copolyester powder, a co-rotating parallel twin-screw extruder is selected, with the following temperatures for each zone: Zone 1 preheating section 100-130℃, Zone 2 melting section 160-180℃, Zone 3 activation section 180-200℃, Zone 4 crosslinking section 200-210℃, Zone 5 homogenizing section 200-210℃, and die head discharge constant temperature section 200-210℃; the entire process involves vacuum degassing and impurity removal, and uniform speed cooling water drawing to prepare copolyester masterbatch granules, which are then thoroughly dried and packaged for later use.
[0093] Injection molding sample preparation: Take 1 part of dry copolyester masterbatch and 9 parts of dry copolyester NPG-PETG HF300N resin granules, and premix them thoroughly; add them to the injection molding machine, preset the injection segment temperature to 220~255℃, the mold constant temperature to 40~60℃, maintain constant temperature and pressure, and cool at a uniform speed to prepare national standard mechanical property test samples and special test plates for optical properties.
[0094] Comparative Example 1 (Blank Baseline)
[0095] Commercially available NPG-PETG HF300N transparent copolyester granules were used alone, without the addition of any end-capping agents, crosslinking agents, anti-hydrolysis agents, antioxidants, or other modifying auxiliaries. Blank standard samples were prepared using the extrusion and injection molding process described in Example 5, serving as a comparative reference group. Experiments revealed that these samples exhibited high transparency but poor chemical resistance, and their delayed melt index fluctuated significantly, exceeding 40%.
[0096] Comparative Example 2 (HMDI control without 1SEB end caps)
[0097] The matrix used was the same NPG-PETG HF300N substrate as in Example 5. 0.6 parts of HMDI isocyanate without 1SEB end-capping and passivation treatment were directly added, along with the same amounts of carbodiimide and phosphite antioxidants as in Example 5. The mixing, extrusion, and injection molding processes were identical to those in Example 5 to verify the performance of the uncapped isocyanate modification. Experiments revealed increased haze and significant fluctuations in the delayed melt index, possibly related to the excessively high activity of the uncapped isocyanate functional groups, leading to gel formation.
[0098] Comparative Example 3 (IPDI without 1SEB header)
[0099] The matrix was uniformly NPG-PETG HF300N, with 0.6 parts of IPDI isocyanate without 1SEB end-capping added directly. All other auxiliary agents, dosages, the entire preparation process, and molding conditions were completely consistent with Example 5 to verify the performance of pure IPDI modification. Experiments revealed increased haze in the samples, and significant fluctuations in the melt index during high-temperature processing. This may be related to the excessively high activity of the unblocked isocyanate functional groups, leading to gel formation.
[0100] Comparative Example 4 (Control without isocyanate synergy, only end-capping 1SEB adjuvant)
[0101] Except for the absence of HMDI / IPDI additives, the same proportion of 1SEB end-capping agent was used instead. Other parameters remained the same as in Example 5: NPG-PETG matrix, equal amount of phosphite antioxidant, and carbodiimide anti-hydrolysis synergist. The mixing, extrusion, and injection molding process parameters were consistent with Example 5. Experiments revealed that the delayed melt index fluctuation was still relatively large, and the improvement in hydrolysis resistance was not significant.
[0102] Comparative Example 5 (Control with only anti-hydrolysis additive and no end-capped isocyanate)
[0103] The matrix used was standard NPG-PETG HF300N. Only an equal amount of aliphatic carbodiimide anti-hydrolysis agent and a matching equal amount of phosphite antioxidant were added, as in Example 5. No 1SEB-terminated isocyanate modifiers were added. The entire process was compared to Example 5 to verify the limitations of using a single anti-hydrolysis agent. Experiments showed that the delayed melt index fluctuation was still relatively large, and while hydrolysis resistance improved, the improvement was not significant.
[0104] Comparative Example 6 (Traditional phenol blocking instead of 1SEB control)
[0105] The overall raw material ratio, matrix type, entire preparation process, and molding conditions were consistent with Example 5, except that a conventional industrial phenol was used to block an equal amount of HMDI isocyanate, replacing the 1SEB end-capping system of this invention, to verify the effect of the conventional phenolic blocking agent on the material properties. The experimental results showed that the sample color was significantly yellowish.
[0106] Figure 3 The images show the typical appearance of pure PETG, modified PETG examples, and comparative examples. It can be seen that the visual differences are clearly visible in the actual photos. The modified transparent sample of this invention is transparent, without yellowing or delamination; the traditional phenol-sealed sample is highly yellow and has excessive haze. The blank PETG sample has good transparency, but its surface is not resistant to chemical etching and is prone to whitening and cracking.
[0107] Comparative Example 7 (Strong chromogenic nitrophenol blocking control)
[0108] All matrix raw materials, additive dosages, equipment conditions, temperature control processes, and molding procedures were consistent with those in Example 5, except that 1SEB was replaced with 2,4-dinitrophenol as the isocyanate blocking agent to verify the effect of traditional blocking agents on the optical and overall properties of transparent polyester. The experiment revealed that the sample had a yellowish tint, decreased transparency, and increased haze.
[0109] Comparative Example 8 (Conventional epoxy crosslinking agent replacing end-capped isocyanate control)
[0110] A commonly used epoxy polymer chain extender was selected and replaced with an equal mass of the 1SEB-terminated isocyanate core modifying component of this invention. The remaining matrix, anti-hydrolysis additives, antioxidants, and processing technology were consistent with Example 5. Experiments revealed that, compared to the dedicated isocyanate crosslinking system, the sample exhibited some gelation, possibly due to the excessively high activity of the epoxy functional groups and the excessively rapid reaction rate at high temperatures, resulting in increased haze. Furthermore, the presence of gel defects led to relatively large fluctuations in the impact strength of the sample.
[0111] The materials prepared in Examples 5 to 16 were subjected to performance tests, and the results are shown in Table 1. The materials prepared in Examples 1 to 8 were subjected to performance tests, and the results are shown in Table 2.
[0112] Table 1. Performance test data of the materials obtained in Examples 5-16
[0113] Table 2 shows the performance test results of the materials prepared in Examples 1-8.
[0114] As shown in the table above, the copolyesters prepared using different copolyester matrices exhibit varying properties, primarily due to differences in the chemical structure of the third monomer used for modification. Example 5 uses NPG-modified PETG as the matrix. Neopentyl glycol (NPG) introduces flexible segments, enhancing the impact toughness of the copolyester, but leading to significant melt index fluctuations. The rigid alicyclic structure of 1,4-cyclohexanediethanol (CHDM) enhances thermal stability and increases the TGA weight loss temperature of the copolyester material (Example 9: CHDM-modified PETG). Examples 10 and 12 use bio-based ISB-modified PCTG and ISB-CHDM bicomponent composite modified PCTG as matrices, respectively. The rigid furan ring of isosorbide (ISB) synergistically with CHDM to form a denser molecular chain stack, requiring higher processing temperatures. Simultaneously, the melt prepared using this matrix exhibits higher melt stability and fewer hydrolysis sites.
[0115] This invention utilizes different aliphatic isocyanates, including HMDI (Example 5), IPDI (Example 7), and a 1:1 mass ratio of HMDI and IPDI blend (Example 11). HMDI has a linear aliphatic structure, exhibiting high -NCO reactivity after desealing and readily reacting with terminal hydroxyl groups. However, excessive crosslinking may lead to localized gelation, resulting in a slight increase in haze of the copolyester material. IPDI's alicyclic structure provides steric hindrance, slowing the reaction rate, enabling more uniform chain extension, and improving light transmittance. The blending of HMDI and IPDI balances reactivity and steric hindrance, reducing the risk of gelation while ensuring chain extension efficiency, with melt index fluctuation ≤20%.
[0116] Comparing Examples 7, 8, 14, and 15, it can be seen that with the increase of the amount of 1SEB-terminated IPDI additive, the melt flow rate of the copolyester material significantly decreases, the high-temperature melt stability and thermogravimetric temperature continuously increase, and the elongation at break significantly increases. Only with an appropriate amount of additive can good optical properties, such as transmittance, haze, and yellowness, be obtained; excessive addition will slightly affect optical uniformity. This is because the de-termining and chain-extending effect of -NCO on the polyester end groups after de-termination, and the formation of a cross-linking network with carbodiimide, maintains high transparency while improving heat resistance, toughness, and resistance to chemical cracking.
[0117] Example 16 of this invention provides a masterbatch process that is slightly superior to direct blending (Example 5) in melt stability and optical performance, and is particularly suitable for high-precision transparent products. The masterbatch uses a high-concentration premix of PETG powder, resulting in finer dispersion of additives in the matrix, more complete unblocking-NCO reaction, more uniform chain extension / crosslinking, smaller melt fluctuations, and higher toughness. Local micro-dispersion differences may occur during masterbatch dilution, leading to a slight increase in haze, but it still meets the requirements of ≥88% transmittance and ≤2.5% haze. The masterbatch process offers more stable storage and transportation, more precise metering, compatibility with mass production lines, better performance consistency, and suitability for industrial scale-up.
[0118] Comparative results show that blank PETG exhibits poor high-temperature melt stability and chemical resistance; direct use of unblocked isocyanate easily leads to gelation and excessive haze; single additives cannot achieve long-term protection; traditional phenolic blocking agents cause severe yellowing and optical performance failure in products; epoxy chain extenders are prone to defects and poor transparency. This invention employs synergistic modification of alicyclic tertiary alcohol-blocked isocyanate with high-molecular-weight carbodiimide, achieving stable storage at room temperature, controllable deblocking at high temperatures, in-situ chain extension and crosslinking, and dual hydrolysis resistance. While ensuring high light transmittance, low haze, and low yellowing, it significantly improves melt stability, heat resistance, and resistance to chemical stress cracking, verifying the uniqueness and necessity of the technical solution.
[0119] In summary, this invention employs a sterically hindered alicyclic tertiary alcohol (such as isoborneol, 1SEB) to end-modify a composite isocyanate system, effectively shielding the -NCO active functional groups. This allows the isocyanate to maintain the reactivity of its active functional groups during room temperature storage, batch mixing, low-temperature drying and preheating, and at 200°C. The modified premixed material can be stored in a sealed environment for a long time without clumping, agglomeration, oxidation, or discoloration. This addresses industry pain points such as short storage and transportation cycles, large batch performance fluctuations, and numerous early side reactions in traditional free isocyanate modification systems, achieving high processing stability of the material in mass production.
[0120] The modified melt exhibits stable and controllable melt flow at high temperatures, resulting in stable injection molding processes. The transparent copolyester synergistically modified according to this invention shows a melt flow rate change rate of ≤20% after a 10-minute residence time at 230°C, representing a 49% increase in melt index compared to the blank pure resin. This significantly narrows the fluctuation range of melt flow properties, effectively suppressing the random thermal degradation of ester bonds in the polyester backbone and the random chain breakage. Melt viscosity remains stable and controllable, and the injection cavity filling speed is uniform. The molded transparent samples show no obvious defects, with a light transmittance greater than 88%, haze less than 2%, and yellowness value less than 3.0. The significantly improved sample appearance enhances processing efficiency.
[0121] Dual protection against hydrolysis and chemical stress cracking: Significantly improved resistance to high temperature and chemical stress cracking. Utilizing the in-situ unblocking of the isocyanate's active functional groups under high-temperature injection molding conditions, combined with the highly efficient hydrolysis-resistant properties of the carbodiimide functional groups, this dual synergistic protection system protects against residual moisture, residual catalysts, and attacks on ester bonds by terminal carboxyl / hydroxyl groups in the polyester, blocking the propagation path of hydrolytic chain reactions. This performance characteristic is suitable for prolonged immersion in high-concentration daily chemical alcohol media, improving the product's resistance to stress microcracks, preventing surface whitening and peeling, and eliminating overall brittle failure. The overall service life of the product is expected to be significantly extended. Compared to pure PETG, which easily whitens and develops microcracks after about 10 hours of immersion in 50% ethanol, the dual synergistic system of this invention maintains basic surface stability under 60-hour immersion conditions.
[0122] The modified material exhibits no significant color-developing byproducts, and maintains long-lasting optical quality with high transparency and low yellowing. The core modified substrate, 1SEB, is heat-resistant and resistant to oxidation and degradation, and does not generate conjugated quinone-type color-developing impurity groups throughout the process, overcoming the potential for yellowing in finished products caused by traditional antioxidant solutions. Furthermore, 1SEB demonstrates excellent thermodynamic compatibility with various types of PETG and PCTG copolyesters, achieving uniform dispersion without agglomeration, interfacial delamination, or small molecule migration and precipitation. The modified product maintains a stable visible light transmittance of ≥88%, with overall haze strictly controlled to ≤2.0%. Its comprehensive optical performance is significantly superior to traditional closed-modification systems such as phenol and nitrophenol, making it suitable for high-transparency applications in food, cosmetics, and optics.
[0123] The modification process of this invention is applicable to the copolymerization modification of PETG and PCTG transparent copolyester substrates with NPG, CHDM, and ISB. During implementation, there is no need to modify existing extrusion and injection molding production lines, the overall incremental modification cost is controllable, there is no environmental pollution pressure, and the prospects for industrialization and promotion are broad.
[0124] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a highly thermally stable transparent copolyester modified with end-capped aliphatic isocyanate, characterized in that: include, Aliphatic isocyanates react with alicyclic tertiary alcohols in the presence of an organotin catalyst to yield end-capped isocyanate intermediates; A modified copolyester is obtained by melt extrusion of a copolyester matrix, a capped isocyanate intermediate, an aliphatic carbodiimide anti-hydrolysis agent, and a phosphite antioxidant in a mass ratio of 100:0.3~1.2:0.1~1.0:0.1~0.
35. The molar ratio of the effective -NCO functional groups of the alicyclic tertiary alcohol to the isocyanate is 2.03 to 2.05:
1.
2. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 1, characterized in that: The aliphatic isocyanate includes one or more of HMDI or IPDI; the alicyclic tertiary alcohol contains only a single tertiary hydroxyl group, without primary hydroxyl groups, secondary hydroxyl groups, acidic functional groups, or aromatic conjugated structures, and includes one or more of saturated bicyclic alicyclic tertiary alcohols, saturated polymethyl substituted monocyclic alicyclic tertiary alcohols, and adamantyl tertiary alcohols.
3. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 2, characterized in that: The aliphatic isocyanate includes one or more of isoborneol, methyl isoborneol, camphenyl tertiary alcohol, and 1-adamantanol.
4. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 3, characterized in that: The organotin catalyst includes dibutyltin dilaurate, added at 0.15 wt% of alicyclic tertiary alcohol; the phosphite antioxidant includes tris(2,4-di-tert-butylphenyl) phosphite.
5. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester according to any one of claims 1 to 4, characterized in that: The reaction is carried out at a rotation speed of 300–500 r / min, a reaction time of 3.0–3.5 h, a temperature of 75–80 °C, and under inert gas protection, the water content of the reaction system is ≤0.05%.
6. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 1, characterized in that: The copolyester matrix is PETG or PCTG modified with a third monomer, wherein the third monomer includes one or more of NPG, CHDM, and ISB.
7. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 6, characterized in that: The aliphatic carbodiimide antihydrolysis agent has a number average molecular weight ≥ 5000.
8. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester according to any one of claims 1 to 4, 6, and 7, characterized in that: The closed mixing process involves a mixing speed of 1000–1500 r / min and a mixing time of 6–12 min.
9. The method for preparing the end-capped aliphatic isocyanate-modified high heat-stable transparent copolyester as described in claim 1, characterized in that: The melt extrusion process includes the following temperature zones: Zone 1 preheating section 150–180°C, Zone 2 melting section 180–200°C, Zones 3–5 200–210°C, and the discharge constant temperature zone 200–210°C.
10. A highly thermally stable transparent copolyester modified with end-capped aliphatic isocyanate, prepared by any one of the preparation methods described in claims 1 to 9, characterized in that: It has the following characteristics: the MFR change rate of the copolyester after being kept at 230℃ for 10 min is ≤20%, the light transmittance is ≥88%, the haze is ≤2.5%, and after being soaked in 50% ethanol solution for 60 hours or more, there is no obvious whitening or micro-cracks.
Citation Information
Patent Citations
Transparent copolyester and its preparation method
CN102924676A
A creep-resistant and hydrolysis-resistant polyester FDY fiber and its preparation method
CN103556291B
A photocurable composition and a hard coating film
CN108753146B
Stably-stored blocked isocyanate composition, and preparation method and application thereof
CN110804146A
